The effects of tamoxifen on TNFR2 in NMU-induced breast cancer rat model - Idris, Ros Akmal Mohd (2025)
The tumor necrosis factor receptor 2 (TNFR2) has been implicated in cancerrelated inflammation and immune responses, yet its role in breast cancer remains unclear. This study aimed to explore the effect of Tamoxifen (TAM) on TNFR2 expression in an N-methyl-N-nitrosourea (NMU)-induced breast cancer rat model, as well as others associated biomarkers (ER, PR, HER2, Bax, Bcl-2). Rats were divided into three groups: healthy controls, NMU-induced positive group, and NMU-induced group treated with TAM. Immunohistochemistry (IHC) was performed to assess biomarkers expression. Results showed that TNFR2 was undetectable in both the Positive and TAM-treated groups, suggesting that TNFR2 may not play a significant role in this NMU-induced breast cancer model. ER and PR levels were found to decrease after TAM treatment, indicating TAM's influence on hormonal receptor signalling in this model. HER2 expression was almost undetectable across all groups, while Bax, a pro-apoptotic marker, showed reduced expression in the positive group meanwhile TAM group shows moderate expression. In contrast, Bcl-2, an antiapoptotic protein, displayed varied expression patterns across the groups. These findings suggest that TAM impacts hormonal receptor signalling and apoptosis regulation but does not appear to influence TNFR2 expression in this NMU-induced breast cancer rat model. This is the first study that investigating the role of TNFR2 with others associated markers in NMU-induced breast cancer rat model.